2006
DOI: 10.1108/09696470610705479
|View full text |Cite
|
Sign up to set email alerts
|

Is trust really social capital? Knowledge sharing in product development projects

Abstract: Purpose -The purpose of this research is to focus on the role of trust in knowledge sharing. Social capital researchers have put forward trust as an important force behind the sharing of knowledge. This study aims to investigate whether trust indeed explains knowledge sharing relationships, or whether there are in fact much more important drivers of the sharing of knowledge in new product development projects. Design/methodology/approach -A survey study was carried out in large new product development projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
174
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(186 citation statements)
references
References 31 publications
4
174
1
7
Order By: Relevance
“…However, they assume trust implied behavioural intentions and therefore did not distinguish trust from trustworthiness. Recently it has been suggested that that trust is more complex and should include aspects of capability, benevolence, and integrity (Bakker et al, 2006), honesty and confidence or credibility (Coote et al, 2003;Coulter and Coulter, 2003).…”
Section: Trust and Commitment Antecedent To Satisfactionmentioning
confidence: 99%
“…However, they assume trust implied behavioural intentions and therefore did not distinguish trust from trustworthiness. Recently it has been suggested that that trust is more complex and should include aspects of capability, benevolence, and integrity (Bakker et al, 2006), honesty and confidence or credibility (Coote et al, 2003;Coulter and Coulter, 2003).…”
Section: Trust and Commitment Antecedent To Satisfactionmentioning
confidence: 99%
“…First, we followed a more differentiated view of trustworthiness and distinguished between ability, benevolence, and integrity (Bakker, Leenders, Gabbay, Kratzer, & Van Engelen, 2006;Mayer et al, 1995). The data pointed to an asymmetry between repatriates as knowledge senders and domestic work unit members as knowledge recipients, regarding the different importance they attached to the underlying trustworthiness dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Badania empiryczne obejmujące problematykę dzielenia się wiedzą w przedsiębior-stwach charakteryzują się cennymi walorami poznawczymi i utylitarnymi. Pomimo że jest ona w Polsce wciąż słabo rozpoznana, jednocześnie dotychczasowe wyniki analiz wskazują, że w obszarze zarządzania wiedzą w przedsiębiorstwach kluczową rolę odgrywają innowacje dotyczące dzielenia się wiedzą 3 . W związku z tym celowe wydaje się wypeł-nienie istniejącej w tym zakresie luki.…”
Section: Wprowadzenieunclassified